2017
DOI: 10.1177/1359105317720818
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of stigma among people affected by early- and late-onset Alzheimer’s disease

Abstract: An exploration of perceptions of stigma among people with early and late-onset Alzheimer's disease and those who support them; using questionnaires (n=44) and semi-structured interviews (n=14). Perceived stigma reporting was low in the questionnaires; whereas interviews revealed higher levels of perceived stigma in the form of unpredictable reactions to diagnosis, feeling stupid, and ignorance of the condition among the public. Perceived stigma was managed in similar ways across age groups; focusing on 'being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 82 publications
3
32
0
Order By: Relevance
“…The ability to go away and 'escape' was often framed as being the 'lucky ones', a theme which was seen across findings on future outlook as well as when discussing stigma around Alzheimer's disease (see Ashworth, 2017). For example, Eva and James (PE1) discuss the benefits of holidays:…”
Section: 'Escapism'mentioning
confidence: 99%
“…The ability to go away and 'escape' was often framed as being the 'lucky ones', a theme which was seen across findings on future outlook as well as when discussing stigma around Alzheimer's disease (see Ashworth, 2017). For example, Eva and James (PE1) discuss the benefits of holidays:…”
Section: 'Escapism'mentioning
confidence: 99%
“…For instance, those living with dementia have reported experiencing various degrees of shame, including avoidance, negative self-perceptions, and uncertainty [2]. Interviews with individuals affected by dementia have shown that these individuals often feel perceived as “stupid” [3]. These perceptions of individuals affected by dementia have been perpetuated by the increased use of the internet as a source of information and social commentary.…”
Section: Introductionmentioning
confidence: 99%
“…In this and other studies, persons with early stage dementia have indicated they are aware of a societal stigma against dementia, causing worry about how others may respond to their diagnoses (Reed & Bluethmann, 2008). Fear of public embarrassment discourages persons living with MCI or early dementia from participation in activities, including exercise (Ashworth, 2017;Cedervall & Arberg, 2010;Husband, 2000). It is likely that improved public education and awareness could reduce stigma (among the public) and fear of stigma (among persons living with MCI or early dementia and care partners) and thereby promote the social participation of persons living with MCI or early dementia in activities such as exercise.…”
Section: Discussionmentioning
confidence: 99%